FAKTOR TERKAIT PARTISIPASI IBU DALAM TES IVA (INSPEKSI VISUAL ASAM ASETAT) DI PUSKESMAS DAERAH TAPANULI SELATAN - Batubara, Anita Agustina; Dame, Elisabeth; Friska, Ernita (Jurnal Inovasi Kesehatan Masyarakat, 2019)
Cervical cancer is a malignant disease of the cervix caused by the HumanPapillomaVirus. In 2012, around 270,000 women died of cervical cancer, more than 85% of these deaths occurred in low and middle income countries. In developed countries cervical cancer is in 10th rank, while in developing countries is still first rank and the main cause is cancer deaths. Coverage of IV examinations and Clinical Breast Examination in North Sumatra Province until 2016 were 130,025 people (7%). Pintupadang Health Center in 2017, mothers who performed IVAs test were 138 people and 116 people in 2018. This figure is still relatively low compared to the annual target (2,047 people in 2018).This type of research use descriptive analytical with a cross sectional approach which aims to determine the factors associated with the participation of mothers for IVA tests at the Pintupadang Health Center. The population in this study were all mothers who visited the Pintupadang Health Center. The sample in this study was 96 respondents, the sample technique was consecutive sampling. Data collection techniques use questionnaires and univariate, bivariate and multivariate data analysis with logistic regression analysis.The results showed that factors related to maternal participation in the IVA test were education (p = 0.037), knowledge (p = 0.002), attitudes (p = 0.010), husband's support (p = 0.007), health care support (p = 0.011) , there was no influence between access to the IVA examination service (p = 0.309) and maternal participation in the IVA test. The most dominant factor is knowledge with p value 0.007 and RP 3.499.It is expected that mothers can increase their knowledge and awareness to carry out IVA tests to detect early cervical cancer.